Collaborative Gaming: Teaching Children About Complex Systems and Collective Behavior. (October 2013) - Peppler, Kylie; Danish, Joshua A.; Phelps, David
Although games—including board games, video games, and Massive Multiplayer Online Games—have garnered significant attention in recent years for their impact on educational outcomes, a primary focus of this interest is the transfer of knowledge from game to nongame settings. Building on this literature, our research explores how game designs that promote either competitive or collaborative play may lead to differential outcomes including dramatically different and social dynamics. Using video transcribed for speech and gesture, we developed a grounded coding scheme to compare the experiences of a group of 40 early elementary students engaged in a uniquely designed board game, called HIVEMIND, to teach advanced science content to young children ages 6 to 9, which were organized around either (a) individual or (b) collective play. Findings indicate that, in collaborative mode, players were significantly more likely to make positive comments to others, talk on-topic, read instructions to other players, gaze toward the board as well as other players, and take shorter turns among other findings. Implications of this work for designing games and promoting collaborative and positive learning experiences are discussed.